Supply Chain Management dan kinerja perusahaan - Widarto J. Rachbini (Journal of Business & Banking, 2017)
Supply Chain Management (SCM) and Corporate Performance are the two interrelated elements. SCM can be the vital factor for improving the corporate performance. This study attempts to determine the effect of Supply Chain Management on the company’s performance. It used 165 manufacturing employees in Indonesia as the sample taken through www.googledocs.com. The analysis was conducted using Structural Equation Modeling (SEM) and processed using Lisrel 8.7. The research proves that information sharing, long term relations, cooperation and integration process, positively and signifi-cantly influence the company's performance. But Long Term Relations, influence the company’s performance.